2009
DOI: 10.1016/j.injury.2009.06.198
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Achilles tendon rupture under endoscopic control

Abstract: The functional outcomes and complications after an endoscopically assisted percutaneous repair of Achilles tendon rupture were evaluated. An arthroscopically assisted percutaneous repair was performed in 20 patients between the ages of 28 and 47 years. Two patients were suffering from a long-standing rupture. Follow-up was 2.5 years. Evaluation entailed Merkel's scale for pain, functional load (weight) bearing capacity, and the heel raise test. For statistical analysis, a random effects Poisson regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Jung et al (47) used a limited open technique and reported a comparatively low rate (3.3%) of sural nerve injury in 2008. Additionally, repair of the Achilles tendon using an endoscopic camera can be useful in determining the initial gap and providing adequate apposition of the tendon ends (48,49). Although Pavic (49) suggested using an endoscopic camera to avoid sural nerve injury, a 2008 study by Fortis et al (48) did not report a significant difference in sural nerve injury rates.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al (47) used a limited open technique and reported a comparatively low rate (3.3%) of sural nerve injury in 2008. Additionally, repair of the Achilles tendon using an endoscopic camera can be useful in determining the initial gap and providing adequate apposition of the tendon ends (48,49). Although Pavic (49) suggested using an endoscopic camera to avoid sural nerve injury, a 2008 study by Fortis et al (48) did not report a significant difference in sural nerve injury rates.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen patients changed their main sports activity because of knee pain (2 patients), fear of re-rupture (4 patients), or busy personal schedule (10 patients). Activities the patients began engaging in included jogging (25), foot-volleyball (19), soccer (11), tennis (10), hiking (9), swimming (6), golf (6), basketball (4), baseball (1), and fencing (1). The earliest return to sports was a patient who was able to play tennis just 10 Ryu et al…”
Section: Functional Resultsmentioning
confidence: 99%
“…Mini open and percutaneous methods have lower rate of infection, but some reports have highlighted an increased incidence of potential sural nerve damage and re-rupture rate due to difficulty in performing suture firmly connecting the edges exactly end to end. 11 Recent studies have shown that no matter which of the abovementioned three surgical technique was applied, there was no difference in functional outcome or patient satisfaction. 12,13 Conservative treatment usually consists of applying a cast for a set period of time.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques allowed good tendon healing and a more rapid return to sport, but sural nerve injury during surgery was a potential complication. 19 Many surgeons have advocated several modifications to the percutaneous or minimally invasive techniques, each with advantages and disadvantages. 10,[20][21][22] The percutaneous repair of the acute Achilles tendon rupture with echographic assistance described here is simple and easily mastered with a short learning curve.…”
Section: Discussionmentioning
confidence: 99%